Peningkatan Hasil Belajar Matematika Siswa Kelas VII-A SMPN 3 Surabaya Melalui Model Kooperatif Teknik Think Pair Share (TPS) - Prasetyo Kurniawan; Suhartono Suhartono; Sunardi Sunardi (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This study aims to improve students' mathematics learning outcomes through the implementation of cooperative learning model using the Think Pair Share (TPS) technique. The subjects of the study were the students of class VII-A at SMPN 3 Surabaya. This Classroom Action Research (CAR) was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through tests, namely formative tests and post-tests. The results showed a significant improvement in students' mathematics learning outcomes after the application of the Think Pair Share technique. In the first cycle, the average student scores increased significantly compared to before the intervention, with even greater improvements observed in the second cycle. Besides improving learning outcomes, the application of the Think Pair Share technique also had a positive impact on student participation and interaction during the learning process. Students became more active in discussions and helped each other understand the lesson material. Therefore, the Think Pair Share technique has proven effective in enhancing the mathematics learning outcomes of students in class VII-A at SMPN 3 Surabaya. .